A Multi-Frequency Replication of the MegaREG Experiments - Alexander, Keith (Journal of Scientific Exploration, 2019)
The MegaREG set of experiments run by the Princeton Engineering Anomalies Research (PEAR) group prior to 2004, found that the response to human intention was positive when the Random Event Generator (REG) bit-rate was 200 bits per trial, but increased in magnitude and was negative in direction when the bit-rate was 2 million bits per trial. This reversal of the influence could not be explained within the existing theories of psi influence, and for several reasons this avenue of investigation was terminated. Given that this effect might represent a clue to the underlying structure of mind over matter influence, the current study set about replicating and extending the MegaREG experiments by examining the influence of human intention over a range of 10 different frequencies from 200 bits per second to 16 million bits per second, on a new, purpose-built REG machine. The study used commercially available REG’s, covered 127 series of 1000 trials each, and was undertaken mainly by 5 operators over a period of 18 months, following protocols largely similar to those of the PEAR study. The results largely confirmed the MegaREG findings of a per-trial increase in effect magnitude with frequency, but were ambiguous with respect to the reversal of effect direction with frequency.